Psychodermatology in Iran: A survey on knowledge, awareness, and practice patterns in Iranian dermatologists. Issue 6 (9th August 2020) - Handjani, Farhad; Saki, Nasrin; Emad, Neda; Hadibarhaghtalab, Maryam; Jafferany, Mohammad
Abstract: Psychodermatology is an interdisciplinary field in dermatology which involves the interaction between mind and skin. Studies from various parts of the world demonstrate generalized lack of knowledge regarding psychocutaneous disorders among dermatologists. We provide this survey to evaluate the knowledge, awareness, and practice patterns of Iranian dermatologists about psychodermatology. A survey questionnaire on the topic of this study was randomly distributed among Iranian dermatologists in a national dermatology conference and also by mail. All collected data were entered into SPSS software version 20.0 and were analyzed using descriptive statistics. The questionnaires were filled out by 65 dermatologists aged 30 to 60 years. From this group, 60% (39) were male and 40% (26) were female. About 86% of the dermatologists saw more than 30 psychodermatology patients weekly and about 43% mentioned they felt somewhat comfortable managing psychodermatology patients. Alopecia, vitiligo, and acne were the most common primary dermatology diseases with secondary psychiatric problems. More than half of our responders mentioned that they did not take any psychodermatology courses during their training program. However, about 66% of the dermatologists expressed interest in participating in psychodermatology continuing medical education programs. Further collaboration between dermatologists and psychiatrists can shape a brilliant future in psychodermatology and improve the quality of life of patients. We highly recommend educational courses in psychodermatology for both dermatologists and psychiatrists.